Genesis and Classification of Termite-Mediated Soils along Toposequences in a Semiarid Area of Southeast Ethiopia. (27th January 2023) - Bekele, Abinet; Beyene, Sheleme; Kiflu, Alemayehu; Yimer, Fantaw
Abstract : Despite the ecosystem functioning they provide, termite pedoturbation along toposequence is overlooked in the genesis of semiarid soils. Therefore, we aimed to describe morphological and physicochemical properties that lead to the classification of termite-mediated soils. In this study, representative pedons, one on each slope class, were described and classified for five different topographical positions, and the soil properties of genetic horizons were compared to those obtained from respective mounds. The result showed that the soils were heavily manipulated by termites except for the pedon at the toe slope. Cambisols were formed on the summit and back slope and resulted from slow pedogenic processes. Luvisols on the toe slope showed redoximorphic features, and gleization and clay synthesis formed the soil, while the upward movement of coarse particles enhanced textural differentiation. Luvisols at the foot of the slope are formed by the partial destruction of iron-bearing minerals accompanied by eluviation-illuviation processes. Accumulation of calcium carbonate following calcification formed Calcisols on the bottom slope. Comparing the mounds and reference pedons, much of the mound's soil is mined from the subsoil, usually from B horizons. However, their influence on soil properties depended mainly on the topography. Moreover, the morphological and physicochemical properties of the studied pedons exhibited various degrees of variation along topography and clearly showed topographic effects. In conclusion, termites can be a potent mediator of soil genesis across toposequences, and their activities should be considered in the classification and management of semiarid soils. A further retrospective examination of micromorphological evidence is recommended to support this finding.